DIDACTIC OPPORTUNITIES OF GAMIFICATION TECHNOLOGIES IN DEVELOPING DIGITAL LITERACY IN THE EDUCATIONAL PROCESS (European Science Methodical Journal, 2026)
This study examines the didactic potential of gamification technologies in developing students’ digital literacy within the educational process. In the era of rapid digitalization, digital literacy has become a fundamental skill for students, enabling them to effectively use digital tools, access information, and participate in modern learning environments. Gamification technologies, including educational games, simulations, and reward-based systems, provide interactive and motivating learning experiences that promote active engagement and skill acquisition. The research analyzes how these technologies can enhance students’ practical digital skills, critical thinking, problem-solving, and collaborative abilities. Furthermore, the study highlights both the opportunities and challenges of integrating gamification into teaching practices. Findings indicate that when implemented thoughtfully, gamification technologies significantly support the development of digital literacy and create learner-centered environments that foster motivation, creativity, and effective learning outcomes.